EMPOWERING EDUCATORS WITH 'SCRATCH': A REFLECTION ON DIGITAL LITERACY TRAINING FOR PRIMARY SCHOOL TEACHERS - Marifatulloh, Sayid; Fajarina, Maskhurin; Zuhriyah, Mukminatus; Agustina, Ria Kamilah; Hardinanto, Eko; Nuruddin, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This article discusses the improvement of digital literacy among elementary school teachers in Indonesia and Malaysia through a Scratch programming workshop. The training program aimed to enhance teachers' abilities to create interactive learning media while addressing challenges in integrating technology into the classroom. Qualitative data were collected through in-depth interviews with three participants, highlighting their experiences, challenges, and the impacts of the training. The findings reveal that the training significantly improved teachers' digital literacy and confidence in using Scratch. However, some challenges, such as understanding coding logic, were noted. This training also positively impacted student engagement through interactive and creative learning tools. The study emphasizes the need for ongoing support, broader training coverage, and collaboration to sustain the benefits of such programs in transforming education